Impact of Age and Storage Duration of Seedling on Yield and Yield Attributes of Wet Season Rice - Saha, P.; Bhuiya, M. S. U.; Karmakar, B.; Salim, M.; Ahmed, B.; Shil, P.; Roy, S. K. (International Journal of Economic Plants, 2018)
Yield and yield components of wet season rice are highly depends on age and storage duration of seedling. Sometimes, farmers are compelled to transplant aged and stored seedlings due to natural calamities like flash flood, flood, drought etc. An experiment was conducted in Agronomy Field, Bangladesh Agricultural University, Mymensingh during July to December 2013 to determine the effect of age and storage duration of seedling on yield and yield components of transplant aman rice. BRRI dhan 52 was used in the experiment. Four seedling age (25, 30, 35 and 40-d old) and four storage durations of uprooted seedlings (0, 1, 2 and 3-d) were laid out in split-plot design with 3 replications. Seedling age, storage duration and their interaction were significant on yield and yield contributing characters such as panicles m-2, grains panicle-1, panicle length, plant height, tillers hill-1 and harvest index. Grain yield gradually decreased along with increased seedling age and storage duration. Seedlings of 25-d-old with 0-d storage duration produced the highest grain yield (6.35 t ha-1) that was at par with 1-d storage seedling (6.15 t ha-1) and thereafter yield reduced dramatically. The highest harvest index (47.1%) was found when 25-d-old seedlings were transplanted and the lowest harvest index(46.5%) was obtained in 40-d-old seedlings. Therefore, 25-d-old seedlings stored up to 1-d after uprooting would be suggested for transplanting to obtain better performance of wet season rice.